Development of a New Smartphone Application to Increase Dietary Compliance in Patients with Chronic Kidney Disease - Bingöl, Feray Gençer; Karadağ, Makbule Gezmen; Bingol, Mustafa Can; Erten, Yasemin (My University, 2022)
Aim: Nutritional therapy in chronic kidney disease (CKD) requires certain regulations in the diet of the patients. Patients’ self-management becomes possible with the development of mobile phones and their software. In the current study, a smartphone application that could be used to increase dietary compliance of CKD stage 4-5 and hemodialysis patients was developed. It is aimed that patients can control the dietary intake of energy, protein, sodium, potassium, phosphorus, and fluid by using the developed mobile application. Subjects and Method: The mobile application has been developed by the researchers until the final control and test phase. Later, the final control and test phase of the developed application were carried out by 5 expert dietitians, 5 specialist doctors, and 5 hemodialysis patients. Results: The majority of the participants stated that the application was easy to use, interesting, visually well designed, contains sufficient reliable information, and that they can recommend it to other patients. Participants who examined the application also offered suggestions about the application. Conclusion: The application was updated according to the evaluations and suggestions of the participants. The final application was formed to be ready for the use of the patients.
Keywords: Hemodialysis; nutrition; chronic kidney disease; mobile technology; Smartphone applications